1969
DOI: 10.1136/bmj.1.5635.23
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum Hypercalcaemia in Treated Hypoparathyroidism

Abstract: Bone Scanning with Strontium-85-Parsons et al.MEDICBL JOURNAL 23 have revealed the presence of bony changes which had been barely visible in previous radiographs. This may reflect the clinicians' poor prediction rather than radiological technique. On occasion, while scanning one area under suspicion another, totally unexpected, area will appear active, and when this is examined radiologically the bony changes are apparent. In this situation scanning has supplemented but in no way replaced radiology. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…These events mandate careful monitoring of serum calcium levels in women with HypoPT who are nursing because hypercalcaemia is commonly encountered if vitamin D analogue therapy is not quickly adjusted. The onset of hypercalcaemia during breastfeeding can be immediate (97,101,102,103,104,105) and has even been reported when treating women with HypoPT with longer-acting ergocalciferol, who did not breastfeed (106). Gradually after weaning, the above changes in maternal hormones regress, and a new steady-state is achieved.…”
Section: Special Circumstancesmentioning
confidence: 99%
“…These events mandate careful monitoring of serum calcium levels in women with HypoPT who are nursing because hypercalcaemia is commonly encountered if vitamin D analogue therapy is not quickly adjusted. The onset of hypercalcaemia during breastfeeding can be immediate (97,101,102,103,104,105) and has even been reported when treating women with HypoPT with longer-acting ergocalciferol, who did not breastfeed (106). Gradually after weaning, the above changes in maternal hormones regress, and a new steady-state is achieved.…”
Section: Special Circumstancesmentioning
confidence: 99%
“…Some reports have found no change in the serum calcium during pregnancy while on a stable dose of calcium with vitamin D or calcitriol (213,264,995), with two of these reporting a small increase in serum calcium in the last few days before delivery (264,995). Since the serum calcium was not adjusted for the serum albumin in these cases (213,264,995), the lack of fall in unadjusted serum calcium during pregnancy may indicate that the ionized calcium had increased.…”
Section: Human Datamentioning
confidence: 99%
“…Since the serum calcium was not adjusted for the serum albumin in these cases (213,264,995), the lack of fall in unadjusted serum calcium during pregnancy may indicate that the ionized calcium had increased. Two reports found that the ionized calcium did not change throughout pregnancy (30,302), but in one of these cases it abruptly fell and became symptomatic during labor (302).…”
Section: Human Datamentioning
confidence: 99%
“…Hypercalcaemia can also occur immediately after delivery in women with hypoparathyroidism treated with vitamin D supplements. 5 6 All these observations support a crucial role for oestrogen in calcium regulation in these women.…”
Section: Commentmentioning
confidence: 58%